Dimerization of Thermomonospora fusca beta-1,4-endoglucanase E2 - McGinnis,K.; Kroupis, C.; Wilson,D.B. (Biochemistry, 1993)
Unboiled Thermomonospora fusca endoglucanase E2 electrophoresed on SDS-polyacrylamide gels migrated in the range of 80-90 kDa, but when boiled it migrated in the 40-42-kDa range. Sedimentation equilibrium centrifugation as well as chemical cross-linking experiments confirmed that E2 is a dimer. The dimer was reversibly dissociated at low pH. The E2 dimer was stable up to 70 degrees C, but began to dissociate at this temperature after a 30-60-min incubation. A nondimerizing mutant was obtained using region-specific chemical mutagenesis. DNA sequencing of this mutant revealed a single base change that substituted Gly for Glu-263. Chemical modification of carboxylic acid residues in E2 disrupted the dimer interaction
Keywords: Actinomycetales; Blotting,Western; Cellulase; chemistry; Cross-Linking Reagents; Disulfides; Electrophoresis,Polyacrylamide Gel; Enzyme Stability; enzymology; Glutaral; Hot Temperature; Hydrogen-Ion Concentration; metabolism; Molecular Weight; Mutation; Oxidation-Reduction; Ultracentrifugation